Individual performance of multi-GNSS signals in the determination of STEC over Thailand with the applicability of Klobuchar model - Seok, Hong Woo; Ansari, Kutubuddin; Panachai, Chaiwat; Jamjareegulgarn, Punyawi (My University, 2022)
Thailand is situated in the southern low latitude region in the Asian longitude sector having much importance as major portion of southern hemisphere is covered by ocean resulting in a sparse density of ground-based monitoring systems. With the establishment of GNSS monitoring stations across the Thailand and neighboring region, it accentuates the ionospheric variability study in the southern hemisphere in the Asian longitude. Therefore, in the current study, we selected four GNSS station located at different part of the country (i.e., CHMA, DPT9, NKRM, and SRTN) and studied the variations of ionospheric slant total electron content (STEC). Here, the STEC observations are estimated by Klobuchar model (namely, Klobuchar-modeled STEC values) and compared with the Global Ionospheric Map (GIM) STEC values for its validation. As an initial study, the Klobuchar-modeled STEC values obtained from five multi-constellation GNSSs over Thailand region (i.e., GPS, GLONASS, Galileo, BeiDou and QZSS) are computed and compared with the GIM STEC values during the intense geomagnetic storm on May 12, 2021 (DOY 132) and during June 2020 to May 2021 for monthly variations. Moreover, to show the relationships between the proposed Klobuchar-modeled STEC values and the GIM STEC values, the correlation coefficients and the root mean square errors between them are computed. The results showed that among the five multi-constellations of GNSSs, the GIM STEC values frequently overestimate the Klobuchar-modeled STEC values, except the QZSS system with the least differences ranging from −10 TECU to 20 TECU. Also, the correlation coefficient between the proposed Klobuchar-modeled and GIM STEC variations span between 0.87 and 0.89, and their RMSEs range from 10 TECU to 11 TECU, excluding QZSS system with less than 10 TECU. The correlation coefficients of higher than 0.85 can be considered as a good indicator for the applicability of Klobuchar model in practice with multi constellation systems.
Keywords: BeiDou; Galileo; GIM; GLONASS; GPS; QZSS; STEC